Introduction - Jaki, Andrzej (Journal of Public Governance, 2024)
In this issue of the Journal of Public Governance, the matter of sustainable development is presented from various perspectives adopted as a starting point for formulating research assumptions by the authors of individual articles.The 21st-century economy is marked by the impact of many economic, social, and political crises. In these conditions, the issue of sustainable development is once again becoming extremely relevant.